AB0267 Five-year safety and efficacy of golimumab in patients with active rheumatoid arthritis despite prior treatment with methotrexate: final study results of the phase 3, randomized placebo-controlled go-forward trial. (23rd January 2014) - Keystone, E.; Genovese, M. C.; Hall, S.; Miranda, P. C.; Bae, S.-C.; Han, C.; Gathany, T.; Zhou, Y.; Xu, S.; Hsia, E. C.
Abstract : Objectives: Final 5yr safety and efficacy results of subcutaneous golimumab (GLM)+/-MTX in a phase 3 trial (GO-FORWARD) of pts with active rheumatoid arthritis (RA) despite MTX therapy are reported. Methods: Pts were randomized to placebo(PBO)+MTX, GLM 100mg+PBO, GLM 50mg+MTX, or GLM 100mg+MTX q4w. PBO+MTX pts crossed over to GLM+MTX at wks 16 (blinded early escape) or 24 (crossover). Pts continued treatment at wk52 (start of long-term extension). After the last pt completed wk52 and unblinding occurred, MTX and corticosteroid use could be adjusted, and a one-time GLM dose increase (50 to 100mg) or decrease (100 to 50mg) was permitted based on investigator judgment. The last GLM injection was at wk252. Observed efficacy results (ACR20/50/70, DAS28-CRP, HAQ-DI, radiographic) by randomized treatment group and cumulative safety data are reported through wks 256 and 268, respectively. Results: A total of 444 pts were randomized; 313 pts continued treatment through wk252, and 131 pts withdrew (64 for AE, 25 for lack of efficacy, 1 protocol violation, 6 lost to follow-up, 32 for other reasons, 3 deaths). 301 completed the safety follow-up through wk268. Efficacy results are presented in the table . At wk256, 76.0% of all pts had an ACR20, 89.5% had a DAS28-CRP EULAR response, and 68.5% had improvement in HAQ-DI ≥0.25. Changes from baseline in mean total vdH-S scores were small; 54% of pts randomized to GLM+MTX had no radiographic progression (ΔvdH-S≤0). The most common AEs were upper respiratory tract infection (32.9%), nasopharyngitis (17.1%), and bronchitis (17.1%); 9.2% of pts had an injection-site reaction. Through wk268, 172/434 pts (39.6%) had an SAE; 14.1% of pts discontinued study agent due to AEs. The rates of serious infections, malignancies, and death were 11.5%, 6.2%, and 1.8%, respectively. Of 429 pts with available samples, 33 (7.7%) were positive for antibodies to GLM. Image/graph: Conclusions: The retention rate was high (70.5%), and improvements in signs/symptoms of RA and in physical function with GLM+MTX therapy were maintained long-term. Radiographic progression appeared controlled with small changes in mean vdH-S scores observed through 5yrs. The long-term safety of GLM is consistent with other anti-TNFα agents. Disclosure of Interest: E. Keystone Grant/research support from: Janssen R&D, LLC, M. Genovese Grant/research support from: Janssen R&D, LLC, S. Hall Grant/research support from: Janssen R&D, LLC, P. Miranda Grant/research support from: Janssen R&D, LLC, S.-C. Bae Grant/research support from: Janssen R&D, LLC, C. Han Shareholder of: Johnson & Johnson, Employee of: Janssen Global Services, LLC, T. Gathany Shareholder of: Johnson & Johnson, Employee of: Janssen Global Services, LLC, Y. Zhou Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, S. Xu Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC, E. Hsia Shareholder of: Johnson & Johnson, Employee of: Janssen R&D, LLC